Grip position affects upper limb kinematic chain during tennis double-handed backhand topspin strokes: considerations for transitioning tennis grip position technique - Busuttil, N. A.; Connolly, M.; Roberts, A. H.; Reid, M.; Dascombe, B. J.; Middleton, K. J. (Sports Biomechanics, 2023)
The purpose of this study was to compare the upper limb kinematic chain of tennis players using either an eastern or continental non-dominant grip position during the forward swing of the double-handed backhand stroke. Sixteen right-handed tennis players performed backhands using two non-dominant grip positions (eastern and continental), aiming for two cross-court zones (deep and short). Trajectory data were captured using sixty reflective markers attached to the upper limb and racket using a 12-camera Vicon motion capture system (250 Hz). Peak angular velocity was significantly greater for multiple joint rotations at the dominant shoulder and entire non-dominant limb in the eastern grip. Subsequently, greater peak racket head angular velocity and post-impact ball speed were generated by the eastern grip, while shot accuracy was similar between grip types. There was delayed dominant shoulder peak adduction angular velocity for the continental grip, possibly due to a lack of skill familiarity causing changes in coordinative patterns. Collectively, the non-dominant grip position appears to influence proximal and distal upper limb movement. Future research should explore upper limb segment coordination comparing preferred and non-preferred double-handed backhand techniques and complete inter-disciplinary investigations to understand what grip positions are most effective for individuals to learn double-handed backhands.